Three-dimensional bundle-like multiwalled carbon nanotubes composite for supercapacitor electrode application. (December 2021) - Hsu, Hao-Lin; Miah, Milon; Saha, Shyamal Kumar; Chen, Jean-Hong; Chen, Lung-Chuan; Hsu, Sheng-Yen
Abstract: Bundle-type mutil-walled carbon nanotubes (MWCNTs) composite electrode is the first investigation and publication for the supercapacitor application. According to the thermogravimetric analysis results, as-synthesized BCNTs are considered as the electrode materials for supercapacitors and electrochemical double-layer capacitor in this study. The Brunauer–Emmett–Teller specific surface area of as-prepared bundled carbon nanotubes (BCNTs) is 95.29 m 2 /g given to a type III isotherm and H3 hysteresis loops. Slow scanning rates promote and enhance to achieve high C b because of the superior conductivity of CNT bundles and one side close-layered Ni/Mg/Mo alloy inside the BCNT-based electrode and facile electron diffusivity between electrolyte and electrode. The specific capacitance C s (1, 560 F/g) is nearly equal to the maximum specific capacitance, which the BCNT-based composite electrode can actually be able to charge or fill in. The maximum energy density value is 195 Wh/kg with corresponding power density values of 0.21 kW/kg. Furthermore, the active 3D BCNTs material fabricated electrode enhances to contact the electrolyte directly and decreases the ion diffusion limitation. Electrochemical impedance spectroscopy spectrum summarized as the low-frequency area controls by mass transfer limitation, and the high-frequency area dominates by charge transfer of kinetic control. After 2, 000 consecutive cyclic voltammetry sacnings and galvanostatic charge-discharge cycles at a current density of 1.67 A/g performs, the specific capacitance retentions of 3D BCNTs electrodes achieved 128.2 and 77.3%, respectively. Three-dimensional BCNT composite electrodes exhibit good conductivity and low charge transfer resistance, which is beneficial to fast charge transfer between the BCNTs electrode materials and electrolytes. Graphical abstract: Image 1 Highlights: Three-dimensional BCNT composite is the first study of supercapacitor electrode application for publication. BCNT electrodes achieve a maximum capacitance of 1, 560 F/g. BCNT electrodes exhibit an energy density of 195 Wh/kg at a power density of 0.21 kW/kg. BCNT electrodes perform specific capacitance retention (128.2%) after 2, 000 continuous cyclic voltammetry cycles.